Analisis Autokorelasi Spasial Balita Stunting Menggunakan Indeks Moran’s I - Rizqia Rahmah Nurul Syifa; Silmi Afina Aliyan; Tiara Handayani (Universitas Pendidikan Ganesha, 2026)
Stunting among toddlers is a public health issue strongly related to socioeconomic conditions and the distribution of healthcare services. This study aims to analyze the spatial distribution of stunting cases in Cirebon City using a spatial analysis approach. Data were obtained from the Cirebon City Statistics Agency and processed using mapping software to identify whether spatial clustering of cases exists. The results show that stunting cases form clusters, particularly in Harjamukti District, which also has a high number of poor residents and birth rates. These findings indicate that the distribution of stunting is not random but concentrated in specific areas. The study recommends identifying priority intervention zones and ensuring the equitable distribution of health personnel, especially nutritionists, as a crucial step toward area-based stunting reduction.